Ocena działań marketingowych prowadzonych w Internecie jako zadanie controllingu działalności marketingowej w warunkach globalizacji - Nowak, Marta (Assessment of marketing actions conducted via internet as a marketing controlling task in the conditions of globalization, 2008)
The paper focuses on the measurement, analysis and assessment of the marketing conducted in Internet. It explains the importance of using Internet as an important market! I during globalization period. The reasons for usage of Internet marketing actions are given. Marketing controlling indicators which assess the Internet marketing actions are presented and explained process of conducting marketing campaign in Internet is presented and the importance and of its effects on each stage are defined.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 325-334